The Role of Sarcolipin and ATP in the Transport of Phosphate Ion into the Sarcoplasmic Reticulum - Becucci, Lucia (The Biophysical Society, 2009)
In a previous study, sarcolipin (SLN) was shown to form channels selective toward chloride ion when incorporated in a mercury-supported tethered bilayer lipid membrane (tBLM). Its incorporation had only a modest permeabilizing effect on phosphate ion. In this note the resistance of a tBLM membrane incorporating sarcolipin was investigated by electrochemical impedance spectroscopy in aqueous solutions of 0.05 M sodium phosphate of pH ranging from 5.3 to 8, in the presence of ATP, adenosine monophosphate, and phenylphosphonic acid. At pH 5.3, submicromolar additions of ATP increase the conductivity of the tBLM incorporating SLN up to a maximum limiting value. The dependence of the conductivity on the ATP concentration satisfies the Michaelis-Menten equation, with an association constant of 0.1 μM. Phenylphosphonium ion and adenosine monophosphate exert an inhibitory effect on membrane permeabilization to phosphate ions by ATP if they are added before ATP, but not if they are added after it. An explanation for this behavior is provided. In conclusion, SLN acts as an ATP-induced phosphate carrier exhibiting a behavior quite similar to that of the unidentified P(i) transporter described previously. No ion-channel activity is exhibited by the T18A mutant of SLN.